2016
DOI: 10.1159/000443143
|View full text |Cite
|
Sign up to set email alerts
|

Co-Existence of Thyroid Nodule and Thyroid Cancer in Children and Adolescents with Hashimoto Thyroiditis: A Single-Center Study

Abstract: Background: Currently, there is an inadequate number of studies on nodule and malignancy development in children and adolescents with Hashimoto thyroiditis (HT). Material and Methods: Patients who were diagnosed with HT between 2004 and 2013 were included in the study. The HT diagnosis was made with a heterogeneous appearance on thyroid ultrasonography and the elevation of antithyroid peroxidase and/or anti-thyroglobulin antibodies. Fine-needle aspiration biopsy (FNAB) was performed in cases with a nodule size… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
21
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 30 publications
5
21
0
1
Order By: Relevance
“…The analysis of US features seen on the thyroid scans revealed that the following five US variants of autoimmune thyroiditis were observed in our group of 179 paediatric patients: the most common in 35.2% diffuse thyroiditis with hypoechogenic background and normoechogenic parenchyma, in 30.2% diffuse thyroiditis with irregular background, in 18.9% nodular variant with normoechogenic irregular background, in 11.7% micronodulations, and in 3.9% diffuse hypoechogenic background. These ultrasound autoimmune thyroiditis features were already described in previous studies [ 9 , 17 20 ] but present classification is, to our knowledge, relatively novel in paediatric patients.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…The analysis of US features seen on the thyroid scans revealed that the following five US variants of autoimmune thyroiditis were observed in our group of 179 paediatric patients: the most common in 35.2% diffuse thyroiditis with hypoechogenic background and normoechogenic parenchyma, in 30.2% diffuse thyroiditis with irregular background, in 18.9% nodular variant with normoechogenic irregular background, in 11.7% micronodulations, and in 3.9% diffuse hypoechogenic background. These ultrasound autoimmune thyroiditis features were already described in previous studies [ 9 , 17 20 ] but present classification is, to our knowledge, relatively novel in paediatric patients.…”
Section: Discussionsupporting
confidence: 70%
“…The association between Hashimoto’s thyroiditis and thyroid cancer has been debated and remains an active area of research and controversy [ 20 , 22 24 ]. If Hashimoto’s thyroiditis could be recognized as a precursor or a risk factor for thyroid cancer, this would have an obvious high clinical impact in paediatric population, given that Hashimoto’s thyroiditis is a rather common disease, with a rising incidence worldwide [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, when considering whether HT is a risk factor for PTC, it is necessary to investigate the levels of TSH. TSH is known to have a trophic effect on follicular-cell thyroid cancer and those of follicular-cell origin 24 . Elevated TSH might potentially increase the risk of thyroid tumour because of TSH-induced proliferation of thyroid cells 25 .…”
Section: Discussionmentioning
confidence: 99%
“…However, for children and adolescents, the association between HT and thyroid cancer seems relatively common. The frequency of PTC in children and adolescents with HT was found variable from 0.67 to ~3% ( 31 33 ). In patients with PTC, the prevalence of coexisting HT varied from 6.3% to more than 40% of the cases.…”
Section: Coexistence Of Thyroid Cancer and Hashimoto's Thyroiditis (Hmentioning
confidence: 98%